Spicer & Pegler's income tax. - Carmichael, K.S.; Pegler, Ernest Charles; Carmichael, Keith Stanley; Great Britain (London : H.F.L., 1972)
This book contains the law relating to companies, in so far as it is applicable to companies rather than to individuals.
First ed. published in 1907 under title: Income tax in relation to accounts.
Includes index
ahz 12/04/2019
Loans
Keywords: Income tax; Business tax